Potential and Management Strategy of Indragiri Hilir Regional Conservation Area (MPA), Riau Province - Lucky Syarif; Efriyeldi Efriyeldi; Trisla Warningsih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
The Indragiri Hilir Regional Conservation Area, Riau Province, has various potentials with high economic value and can be used sustainably. The effectiveness of conservation area management is determined by aspects and factors from inside and outside the conservation area. This study aims to (1) identify the potential of the Indragiri Hilir Regional Conservation Area; (2) analyze internal factors and external factors in the management of regional conservation areas (KKD); (3) formulate the main strategies and alternative strategies in effective management of regional conservation areas in Indragiri Hilir Regency. The survey method was used in this study. The data collected consists of primary data and secondary data; the management strategy of the Indragiri Hilir Regional Conservation Area is carried out using SWOT Analysis and AHP analysis. The study results show that the potential of the Indragiri Hilir KKD area consists of human capital, natural resources capital, artificial capital, and social and economic potential. Internal factors in the management of regional conservation areas consist of community openness in improving an area, the commitment of the Central Government, the commitment of the Riau Provincial Government, the commitment of the Regency Government, local wisdom, the availability of potential natural resources, the number of population human resources, the quality of community human resources, coordination and communication, regional development directions and policies, legal instruments, and law enforcement. External factors consist of SDGs, government programs based on natural resource conservation, corporate involvement in environmental planning, participation of community empowerment companies, research and community-based community service, sectoral ego and spatial ego attitudes, land degradation and ecosystem damage, economic liberalization and political interests, moral hazard actions of stakeholders.